KARAKTERISTIK, KEPATUHAN MINUM OBAT DAN GAMBARAN TEKANAN DARAH PENDERITA HIPERTENSI - Lestari Eko Darwati; Setianingsih; Siti Nur Asiyah (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2022)
Hypertension is said to be the silent killer because it often has no symptoms and tends to be left uncontrolled. Management of hypertension such as dietary compliance, adherence to taking hypertension medication, and environmental modification are important things that can control hypertension which in turn can prevent complications. The purpose of this study was to determine the description of medication adherence and changes in blood pressure in patients with hypertension. This study used a descriptive survey design, a sample of 57 patients with hypertension, the sampling technique used the total population. Statistical analysis using frequency distribution. The results showed that the middle age of hypertensive patients was 54 years, male 57.9%, graduated from elementary school 50.9%, and worked as laborers 38.6%, adhered to hypertension medication 54.4%, the mean initial blood pressure systole 190.00 mmHg and diastolic 90.00 mmHg while the final systolic blood pressure is 140.00 mmHg and diastole is 80.00 mmHg. It is recommended that nurses provide continuous information and motivation to respondents about the importance of being obedient or obedient in taking hypertension drugs.